2018
DOI: 10.1159/000495823
|View full text |Cite
|
Sign up to set email alerts
|

High Circulating Alarin Levels Are Associated with Presence of Metabolic Syndrome

Abstract: Background/Aims: Alarin has been reported to be related with increased food intake and body weight. The relationship of circulating Alarin with insulin resistance or metabolic syndrome (MetS), however, is unknown. This study aimed to investigate the physiological role of Alarin and its association with MetS in humans. Methods: Newly diagnosed MetS patients (n=237) and age-matched healthy subjects (n=192) were recruited for this study. Oral glucose tolerance test, treadmill exercise, lipid infusions and euglyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…A positive correlation was observed between alarin levels and fasting glucose levels, glycosylated hemoglobin (HbA1c) levels, and Homeostatic Model Assessment of Insulin Resistance (HOMA-IR). 21 PCOS is accompanied by dyslipidemia, central obesity, and insulin resistance, similar to MetS. As in MetS, alarin levels were demonstrated to be higher in patients with PCOS in previous studies.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…A positive correlation was observed between alarin levels and fasting glucose levels, glycosylated hemoglobin (HbA1c) levels, and Homeostatic Model Assessment of Insulin Resistance (HOMA-IR). 21 PCOS is accompanied by dyslipidemia, central obesity, and insulin resistance, similar to MetS. As in MetS, alarin levels were demonstrated to be higher in patients with PCOS in previous studies.…”
Section: Discussionmentioning
confidence: 77%
“…In human studies, circulating alarin levels were found higher in women diagnosed as having metabolic syndrome (MetS). A positive correlation was observed between alarin levels and fasting glucose levels, glycosylated hemoglobin (HbA1c) levels, and Homeostatic Model Assessment of Insulin Resistance (HOMA‐IR) 21 . PCOS is accompanied by dyslipidemia, central obesity, and insulin resistance, similar to MetS.…”
Section: Discussionmentioning
confidence: 99%
“…Free fatty acid (FFA) was measured with a commercial kit (Randox Laboratories). Total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C) were analyzed enzymatically using an autoanalyzer (Hitachi) as in a previous report [19]. Serum hormonal levels including total testosterone (TEST), follicle-stimulating hormone (FSH), estradiol (E2) and luteinizing hormone (LH) were examined with electrochemiluminescence immunoassay using COBAS E immunoassay analyzers (Roche Diagnostics GmbH).…”
Section: Biochemical and Hormone Measurementsmentioning
confidence: 99%
“…In vivo studies have also reported that Alarin may be released in response to metabolic stress factors such as abdominal obesity, insulin resistance, dyslipidemia, hyperglycemia, and hypertension. [ 19 ]. In patients with metabolic syndrome and obesity, Alarin levels have been determined to be higher than those of control groups.…”
Section: Discussionmentioning
confidence: 99%